ScienceWorld: Is your Agent Smarter than a 5th Grader? - Wang, Ruoyao; Jansen, Peter; Côté, Marc-Alexandre; Ammanabrolu, Prithviraj (Science World, 2022)
No, it is not. Yet. This new benchmark aims at testing the scientific reasoning abilities of contemporary interactive and grounded text agents at the level of a standard North American elementary school curriculum. Despite the recent transformer-based progress seen in adjacent fields such as question-answering, scientific text processing, and the wider area of natural language processing, we find that current state-of-the-art models are unable to reason about or explain learned science concepts in novel contexts — e.g. models can easily answer what the conductivity of a previously seen material is but struggle when asked how they would conduct an experiment in a grounded, interactive environment to find the conductivity of an unknown material. This begs the question of whether current models are simply retrieving answers by way of seeing a large number of similar input examples or if they have learned to reason about concepts in a reusable manner. We hypothesize that agents need to be grounded in interactive environments to achieve such reasoning capabilities. Our experiments provide empirical evidence supporting this hypothesis—finding that an 1.5 million parameter grounded agent trained interactively for 100k steps can outperform a 11 billion parameter model statically trained for scientific question-answering and reasoning via millions of expert demonstrations.